Liquid Biopsy in Precision Oncology: Clinical Applications of Circulating Tumor DNA and Circulating Tumor Cells - Prabhat Ganju (Indian Journal of Medical and Paediatric Oncology, 2026)
Abstract The advent of “liquid biopsy” as a tool for the detection of molecular abnormalities has paved the way for its use not only in diagnosis but also in screening, monitoring of therapeutic response, and surveillance. Detection of circulating tumor deoxyribonucleic acid and circulating tumor cells are among the commonly employed liquid biopsy targets that are changing the diagnostic and treatment landscape. By offering a minimally invasive method for disease monitoring and aiding treatment decision-making, liquid biopsy techniques are increasingly being incorporated into clinical management algorithms for multiple malignancies.